Pengaruh Citra Merek, Pesan Kelangkaan dan Suasana Toko Terhadap Pembelian Impulsif pada Konsumen Miniso Summarecon Mall Bekasi - Azka Zulfa Aulia; Andrian Andrian (Indo Publishing, 2026)
This study aimed to examine the influence of brand image, scarcity messaging, and store atmosphere on impulsive purchasing among consumers at Miniso Summarecon Mall Bekasi. A quantitative approach was employed using questionnaires distributed to 105 respondents who had previously shopped at the store. Data were analyzed using IBM SPSS Statistics 27 through validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results showed that brand image had a positive but insignificant effect on impulsive purchasing (Sig. = 0.271), while scarcity messaging had a positive and significant effect (Sig. < 0.001) and emerged as the strongest predictor of impulse buying. Store atmosphere had a negative and insignificant effect (Sig. = 0.787). Simultaneously, the three independent variables significantly influenced impulsive purchasing (Sig. < 0.001). The coefficient of determination (R² = 0.360) indicated that the variables explained 36.0% of the variance in impulsive purchasing, while the remaining 64.0% was influenced by other factors outside the scope of this study. These findings suggest that scarcity messaging is an effective marketing strategy for encouraging impulse buying by creating a sense of urgency and limited availability. The study provides practical insights for retailers seeking to enhance consumer.